Answer:
a. f(-1)=12
b. f(2t)=16t²-6t+5
c. f(t-2)=4t²-19t+27
Explanation:
For a, b, c, we are given an input. We plug that into f(x) to find our answers.
a. f(-1)=12
f(-1)=4(-1)²-3(-1)+5
f(-1)=4+3+5
f(-1)=12
-------------------------------------------------------------------------------------------------------------
b. f(2t)=16t²-6t+5
f(2t)=4(2t)²-3(2t)+5
f(2t)=4(4t²)-6t+5
f(2t)=16t²-6t+5
-------------------------------------------------------------------------------------------------------------
c. f(t-2)=4t²-19t+27
f(t-2)=4(t-2)²-3(t-2)+5
f(t-2)=4(t²-4t+4)-3t+6+5
f(t-2)=4t²-16t+16-3t+6+5
f(t-2)=4t²-19t+27